Selected aspects of informatisation of judicial enforcement proceedings - Kinga Luiza Flaga-Gieruszyńska (Journal of Modern Science, 2023)
Objectives The aim of the study is to present an advanced process of informatisation of court enforcement proceedings, which is a derivative of the progressive computerisation of social life. As part of the considerations presented, not only the provisions of the Code of Civil Procedure relating directly to enforcement actions carried out in enforcement proceedings, but also the provisions of laws governing the profession of bailiff, will be analysed.